Intelligent executing mechanism of fuel gas segmented valve - REN XIAOLIN; CAI XINLEI; YANG YIFAN; DU JIANHE; GAO YAOZHOU; ZHANG YANG; WANG GAOFENG (2024)
The utility model provides an intelligent executing mechanism of a fuel gas segmented valve. The intelligent executing mechanism of the fuel gas segmented valve comprises a bottom shell, a connecting flange is arranged at the bottom of the bottom shell, a two-position three-way electromagnetic valve set is fixedly installed in the bottom shell and connected with a pneumatic motor, an output shaft of the pneumatic motor is connected with a speed reducer, the speed reducer is installed in the bottom shell, and the speed reducer is connected with a motor. The speed reducer is provided with a driving shaft, the pneumatic motor is connected with the driving shaft through the speed reducer, the driving shaft is used for being connected with a valve, the bottom end of the driving shaft extends out of the connecting flange, the speed reducer is provided with a limiting stopper, and one side of the limiting stopper is provided with a valve position sensor connected with the speed reducer. The intelligent executing mec